INFLASI, NILAI TUKAR, SUKU BUNGA, TERHADAP RISIKO SISTEMATIS PADA PERUSAHAAN SUB-SEKTOR FOOD AND BEVERAGE DI BURSA EFEK INDONESIA - Elliza Dianita Anas; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this study is to find out and analyze whether inflation, exchange rates, interest rates have a partial and simultaneous effect on systematic risk in the food and beverage sub-sector companies on the Indonesia Stock Exchange (IDX). The population in this study were all companies in the food and beverage sub-sector of the Indonesia Stock Exchange for the period 2012-2017. The sample in this study was determined using purposive sampling and obtained a sample of 12 companies which were used as criteria in the research of the food and beverage sub-sector companies listed on the Indonesian Stock Exchange with a period of 2012-2017. The data obtained in this study is from the official website of Indonesian Stock Exchange (www.idx.co.id) and the official Bank Indonesia website (www.bi.go.id)The analytical method used in this study is descriptive statistics, multiple linear regression analysis, normality test, classic assumption test, and hypothesis testing. From the results of this study it was obtained (1) F value of 110,248 with F significance value that is equal to (0,000) which is smaller than 0.05 with conclusions simultaneously independent variables significantly influence the dependent variable. (2) R2 value is 0.829 or equal to 82.9%. This result means there is an effect of the independent variable of inflation, exchange rate, interest rate on systematic dependent variable, while the remainder of 82.9% is 17.1% influenced by other variables outside this regression model such as country risk, political risk, market risk. (3) Partially independent variables of inflation have a positive significant effect on systematic risk, the exchange rate has a significant negative effect on systematic risk and interest rates have a significant negative effect on systematic risk. Keywords: Inflation, Exchange Rate, Interest Rate, Systematic Risk